Educational Games and the Potential of AI to Transform Writing Across the Curriculum - Anya S. Evmenova; Kelley Regan; Reagan Mergen; Roba Hrisseh (Education Sciences)
Game-based learning has emerged as a promising tool in education, particularly for students with disabilities. Educational games can significantly enhance student engagement, motivation, and skill development across subjects by providing personalized learning experiences and immediate feedback. New developments in generative AI offer opportunities to embed advanced features into educational games. Drawing on focus group insights from educators and families (N = 21), we highlight the key features that teachers and parents want to see in educational games. We then discuss how generative AI can potentially supplement and ensure that those key features are included. A case study of applying these features to a game-based tool to support writing across curriculum is provided. This article offers a glimpse into the informal exploration phase of a larger design research project aimed to develop a proof-of-concept for an intervention that builds a bridge between AI, educational games, and scaffolding STEM content for students with all abilities.